Estudo do desempenho de cabos do tipo optical ground wire (OPGW) quando submetidos aos ensaios de descargas atmosféricas e curto-circuito - Borduchi, Felipe Cordeiro (2013)
This study of course conclusion makes an analysis about ground wires with optical fibers used in overhead transmission lines of electric power. Also called cables type Optical Ground Wire (OPGW), the scope of this study will be a general approach of construction this type of cable, current applications, including planning and government incentives, theory of optical fibers, simulation using software for OPGW cables projects in an Electric Power System (EPS), and especially the analysis of atmospheric discharge and short circuit tests that are applied to the cables, which are parameterized by regulatory standards, which will also be presented. The protection of the EPS together with the transmission of high speed data, forms a pair innovative and technological and changes, surprisingly, what was once thought impossible: reliability and quality in the delivery of electricity from the power utilities to reach the end consumer keeping the stability of the system, and also the high-speed data transfer with little loss of potency to travel long distances. OPGW cables emerged aiming precisely to address these dilemmas, with technological systems, promising and simply manageable. To guarantee compliance with these activities, the protection of EPS and data transmission with low signal loss, it is essential the application of standardized tests on cables, simulating the real effects. Therefore, the study makes a further approach in the analysis of trials of atmospheric discharge and short circuit, in order to check the behavior of OPGW cables in a real situation.